Agatha Christie's Miss Marple Volume 3 [videorecording (DVD)] : A Caribbean mystery ; At Bertram's hotel ; Nemesis ; Sleeping murder - Christie, Agatha, 1890-1976; Christie, Agatha, 1890-1976; Christie, Agatha, 1890-1976; Christie, Agatha, 1890-1976; Hickson, Joan, 1906-1998 (BBC Worldwide Americas, 2015)
Never one to sit idle, Miss Marple finds her luxurious Barbados vacation a bit dull until Major Palgrave's murder turns it into A Caribbean Mystery. Her London stay seems a bit too perfect until she discovers something sinister behind the Edwardian façade At Bertram's Hotel. How can Miss Marple resist visiting the seaside villa of a young couple plagued by terrifying memories of a Sleeping Murder? And how will she solve an unspecified crime in Nemesis, when her only clue is a ticket for a tour of historic homes and gardens, pre-paid by a dead man? Four suspenseful dramas with superb casts and meticulous period detail.